Batillipes (Tardigrada, Arthrotardigrada) from the Portuguese coast with the description of two new species and a new dichotomous key for all species - Santos, Erika (2018)
Five species of Batillipes Richters, 1909 were collected from subtidal sediments of the Portuguese coast. Two of them, B. algharbensis sp. nov. and B. lusitanus sp. nov., are new to science. Batillipes algharbensis sp. nov. differs from all the other Batillipes species in having the middle toes 3 on the fourth feet longer than middle toes 4 and by the presence of rounded lateral body projections between legs III and IV. Batillipes lusitanus sp. nov. has the middle toes of the fourth feet equal in length, but it exhibits a dorsal cuticular ornamentation, constituted by large pillars, similar to the cuticle of B. adriaticus Grimaldi de Zio, Morone De Lucia, D’Addabbo Gallo & Grimaldi, 1979 and B. roscoffensis Kristensen, 1978. However, contrary to B. adriaticus, the caudal apparatus of B. lusitanus sp. nov. is a roundish cuticular expansion and B. roscoffensis lacks caudal apparatus. Batillipes adriaticus and B. phreaticus Renaud-Debyser, 1959 are new records for Portugal. Based on the examination of specimens of B. phreaticus collected at the Portuguese coast and their comparison with type material of this species and also of B. littoralis Renaud-Debyser, 1959, the toe arrangement patterns in species of Batillipes are clarified and a new identification key to species of this genus is provided.